ANALISIS POLA ASUH GIZI PADA BALITA GIZI KURANG - Muhammad Rahmad; Tri Krianto Karjoso; Emy Leonita; Novita Rany; Irwan Muryanto (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Nutritional parenting is part of the parenting style which includes household practices which are realized by the availability of food as well as health care and other sources for the child's survival, growth and development. One of the causes of malnutrition is the pattern of mother's care for toddlers, especially in terms of family nutritional intake, from food preparation, selection of food ingredients, to food menus. The purpose of this study was to obtain in-depth information about how nutrition parenting for malnourished toddlers in the working area of Sungai Parit Public Health Center, Indragiri Hulu Regency. Method: This is a qualitative analytic study with a phenomenal design. The data were collected by conducting in-depth interviews, observation and document review. The number of informants in this study amounted to 13 people, divided into 4 main informants (main caregiver / mother), and 9 supporting informants (4 families, 4 people in charge of the nutrition program, 1 cadre). Result: The mothers' lack of knowledge about nutritional care, the practice of giving complementary breastfeeding and dietary arrangements for children is still low, the implementation of health services utilization and poor sanitation implementation is still not good. Conclusion : The implementation of nutrition parenting in the ditch river community health center is not good, this is due to the low knowledge of mothers about nutrition parenting, the low level of exclusive breastfeeding for toddlers, the inaccurate practice of giving complementary breastfeeding to children, less varied dietary arrangements, application of utilization of health services that are not yet good and the implementation of environmental sanitation is still poor.